2017
DOI: 10.1016/j.jvs.2017.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Morphological suitability for endovascular repair, non-intervention rates, and operative mortality in women and men assessed for intact abdominal aortic aneurysm repair: systematic reviews with meta-analysis

Abstract: 1 ArticlesMorphological suitability for endovascular repair, non-intervention rates, and operative mortality in women and men assessed for intact abdominal aortic aneurysm repair: systematic reviews with meta-analysis Pinar Ulug, Michael J Sweeting, Regula S von Allmen, Simon G Thompson, Janet T Powell, on behalf of the SWAN collaborators* Summary Background Prognosis for women with abdominal aortic aneurysm might be worse than the prognosis for men. We aimed to systematically quantify the differences in outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…A systematic review and meta‐analysis of sex differences in outcome in patients with intact AAA had similar results to the present study, showing that men were 2·27 times more likely to receive aneurysm repair than women. Earlier studies of patients with rAAA in the 1990s and the beginning of the 21st century reported a disadvantage for women with regard to repair rates.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A systematic review and meta‐analysis of sex differences in outcome in patients with intact AAA had similar results to the present study, showing that men were 2·27 times more likely to receive aneurysm repair than women. Earlier studies of patients with rAAA in the 1990s and the beginning of the 21st century reported a disadvantage for women with regard to repair rates.…”
Section: Discussionsupporting
confidence: 84%
“…Abdominal aortic aneurysm (AAA) is four to six times more common in men than in women, but women have an increased risk of rupture at smaller aneurysm diameter. For intact AAA, women are less often eligible for endovascular aortic repair (EVAR) and have worse outcomes, but such sex differences are debated regarding patients with ruptured AAA (rAAA). Although the incidence of rAAA seems to be declining in general, it is unclear whether this is true for both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to suggest specific reasons for lower repair rates in women; further studies are needed to explore this issue. Evidence from studies that examined non‐intervention decisions for elective AAA suggest that women not offered elective repair either had unfavourable anatomy for EVAR or suffered from severe co‐morbidities that increased their risk of death after open repair. In the same interval, vascular services underwent a quality improvement programme in the UK with a focus on improving elective AAA outcomes and reducing the in‐hospital mortality rate to less than 3 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…This was because the prevalence of AAA is higher in men, and the randomized controlled studies that investigated screening for AAA either did not include women or were underpowered to examine the benefit of screening in women. Evidence from observational studies has demonstrated that, when an AAA is found incidentally, the turn‐down rate for elective surgery is significantly higher in women.…”
Section: Introductionmentioning
confidence: 99%
“…As with most atherosclerotic clinical trials, women have been underrepresented in AAA trials. Due to smaller iliac artery dimensions, short aortic aneurysm neck length, and excessive angulation, only 34% of women are suitable for EVAR . The ongoing LUCY Trial (TriVascular Evaluation of Females Who Are Underrepresented Candidates for AAA Repair) is a prospective, nonrandomized, multicenter registry to evaluate a low‐profile endovascular treatment in female patients…”
Section: Evidence‐based Managementmentioning
confidence: 99%